Use of antiserum to neurotensin reveals a physiological role for the peptide in rat prolactin release. - Vijayan, E (1988)
Previous studies have indicated that the brain peptide neurotensin can stimulate prolactin release by direct action on the pituitary gland, whereas its action within the hypothalamus is inhibitory. The inhibitory action is mediated by the release of dopamine into the hypophyseal portal veins, which deliver the neurotransmitter to the anterior pituitary gland to inhibit prolactin release. Our experiments were done to evaluate the physiologic significance of these neurotensin actions by injecting the globulin fraction of highly specific neurotensin antiserum either intravenously or intraventricularly. Injection into the third ventricle of either 1 or 3 microliter of neurotensin antiserum significantly increased plasma prolactin concentrations in (i) ovariectomized and (ii) ovariectomized estrogen- and progesterone-primed rats within 1 hr of injection. The response was more pronounced in the ovariectomized than in the ovariectomized estrogen- and progesterone-treated animals and was dose related. Intraventricular injection of these doses of neurotensin antiserum also evoked elevations in plasma prolactin in intact males, which were significant but smaller in magnitude than those seen in female rats. To evaluate the effect of the antiserum on the pituitary directly, the antiserum was injected intravenously at a dose of 40 microliter, which was sufficient to block the blood pressure-lowering effect of neurotensin. After the intravenous injection of antiserum, a highly significant suppression of plasma prolactin occurred, detectable when first measured at 1 hr after injection in both ovariectomized and ovariectomized estrogen- and progesterone-treated animals; however, the intravenous injection of antiserum had no significant effect on the prolactin release in males. These data indicate the physiological significance of the hypothalamic inhibitory actions of neurotensin on prolactin release, which are probably mediated by its stimulation of dopamine release that in turn, inhibits prolactin secretion by the lactotropes. The direct stimulatory effect of the peptide on prolactin release after its presumed release into portal vessels also appears to be physiologically significant in female but not in male rats.